Memory for self-performed actions in individuals with Asperger syndrome. - Tiziana Zalla (Public Library of Science (PLoS), 2010)
Memory for action is enhanced if individuals are allowed to perform the corresponding movements, compared to when they simply listen to them (enactment effect). Previous studies have shown that individuals with Autism Spectrum Disorders (ASD) have difficulties with processes involving the self, such as autobiographical memories and self performed actions. The present study aimed at assessing memory for action in Asperger Syndrome (AS). We investigated whether adults with AS would benefit from the enactment effect when recalling a list of previously performed items vs. items that were only visually and verbally experienced through three experimental tasks (Free Recall, Old/New Recognition and Source Memory). The results showed that while performance on Recognition and Source Memory tasks was preserved in individuals with AS, the enactment effect for self-performed actions was not consistently present, as revealed by the lower number of performed actions being recalled on the Free Recall test, as compared to adults with typical development. Subtle difficulties in encoding specific motor and proprioceptive signals during action execution in individuals with AS might affect retrieval of relevant personal episodic information. These disturbances might be associated to an impaired action monitoring system.